CFD simulation and experiment on the flow field of air-assisted ultra-low-volume sprayers in facilities - Lu, Xinyu; Gong, Yan; Liu, Dejiang; Wang, Guo; Chen, Xiao; Zhang, Xiao; Liang, Qiuhan (International Journal of Agricultural and Biological Engineering, 2021)
In order to explore the performance of the B-ULV-616A knapsack sprayer, computational fluid dynamics (CFD) was used to simulate the B-ULV-616A knapsack air-assisted device, which features an ultra-low-volume electric sprayer. Field experiments were carried out to test the spraying effects, and the KANOMAX anemometer was used to verify the simulated results. First, the internal and external flow fields and droplet deposition distribution of the ultra-low-volume sprayer were established. The results showed that the air-assisted spray device can change the airflow speed and direction and produce a high-speed swirling airflow at the outlet of the air-assisted spray device. The high-speed airflow (maximum of 83.5 m/s) generates negative pressure (minimum of 0.099 MPa) and causes a rapid increase in the droplet velocity and a secondary droplets spray, allowing droplets to reach a longer distance. Then, the maximum relative error was 20.14%, and its average value was 9.59%, indicating that the CFD method is suitable for the flow field analysis of the air-assisted spray device. Finally, based on the greenhouse experiment, the knapsack air-assisted ultra-low-volume electric sprayer was found to effectively improve the deposition on the rear of the crop, increase the droplet density (maximum of 81/cm2; droplet density of conventional electric sprayer is 64/cm2), and reduce the deposition amount and coefficient of variation (below 20%) within and between regions. Further, it managed to reduce pesticide use (by 69.85%) and rural non-point source pollution.Keywords: CFD simulation, air-assisted sprayer, ultra-low spraying rate, deposition, air-velocity field, relative errorDOI: 10.25165/j.ijabe.20211402.6013Citation: Lu X Y, Gong Y, Liu D J, Wang G, Chen X, Zhang X, et al. CFD simulation and experiment on the flow field of air-assisted ultra-low-volume sprayers in facilities. Int J Agric & Biol Eng, 2021; 14(2): 26–34.